MAQASID AL-SHARIAH SEBAGAI KERANGKA KETAHANAN KELUARGA DIGITAL: MENGONSTRUKSI ULANG DAMPAK MEDIA SOSIAL TERHADAP KELUARGA MUSLIM - Ririn Aprinda; Tianshi Ahwal Ramadhani; Akbar Umar; Muhammad Yadri Abrar (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2026)
This study aims to examine the impact of social media use on the resilience of Muslim families in Indonesia through the perspective of Maqashid Syariah. The increasing penetration of social media has significantly changed patterns of interaction, communication, and values ​​within the family institution. The method used is a systematic literature review guided by PRISMA, analyzing 45 reputable scientific articles published between 2019 and 2024 from the Scopus, Web of Science, and Google Scholar databases. The results of the study indicate that social media has a dual impact: on the one hand, it facilitates the strengthening of communication and access to Islamic information, but on the other hand, it poses a serious threat to the five principles of Maqashid Syariah, namely the protection of religion (hifz al-din), life (hifz al-nafs), reason (hifz al-aql), descendants (hifz al-nasl), and property (hifz al-mal). This article produces an original conceptual model that positions Maqashid Syariah as an evaluative filter between social media penetration and the resilience of Muslim families, while also formulating a three-layered strengthening strategy: Islamic digital literacy, family social media governance, and revitalization of religious institutions. The contribution of this article is to fill the research gap by integrating the theological-juridical framework of Maqashid Syariah in the analysis of the impact of social media on Indonesian Muslim families, which has not been done systematically before.